Optimum dietary crude protein level for growth in South African abalone (Haliotis midae L.) - Sales, J.; Truter, P.J.; Britz, P.J. (Aquaculture nutrition, 2003)
A 95‐day feeding trial was conducted to evaluate the effects of dietary crude protein level on total body weight gain and protein gain of juvenile (4.89 ± 0.57 g) South African abalone (Haliotis midae). Six semi‐purified diets containing casein, fish meal and cottonseed meal as protein sources, and with crude protein levels ranging from 54.8 to 479.2 g kg−1 dry matter (DM), were fed to four tanks containing 30 abalone each in a continuous flow system. No differences (P > 0.05) were found in moisture, ash or lipid content of soft‐body tissue as dietary crude protein level increased, indicating that differences (P < 0.05) in soft‐body protein content were solely due to dietary crude protein level. The relationships between dietary crude protein level and total body weight gain and protein gain were analysed by broken‐line and second‐order polynomial regression models. Based on total body weight gain, 358.7 g kg−1 DM dietary protein from good quality sources is recommended for maximum growth of juvenile H. midae, while, if dietary protein is reduced to 280.7 g kg−1 DM, growth will be depressed with 5 g kg−1.